The Role of Other Social Beings in Metacognition: How it Defines and How it can be Done for Kindergarden Classroom - Ma, Wen; Wang, Xiufang; Zhang, Bo (Progress in Language, Literature and Education Research Vol. 6, 2024)
First, Kontos’s study explained how parent-child interaction is a necessary precursor to the child’s development of metacognitive skill [1]. In a second study, Gauvain and Rogoff [2] conducted two studies examining the collaborative problem solving among adult-child, child-child and individual child and its impact on children’s solo planning skills. A third study, Harris, Kupinski, and Johnson [3] assessed the influence of maternal teaching on the preschoolers’ categorization knowledge. A fourth study, Perry and her colleagues carried out a qualitative study exploring the teaching-learning contexts and how they fostered learners’ development of self-regulated learning [4]. Finally, Larkin [5] studied how collaborative group work among peers influenced the development of individual metacognitive processing. Collectively, the studies suggest that joint activities create spaces for children to develop metacognitive experience.